DESIGNING LEARNING MATERIALS FOR TEACHING STUDENTS OF ENGLISH VILLAGE AT PARIT NANAS KELURAHAN SIANTAN HULU - STEVANI SAIMIMA; Sahrawi Sahrawi; Abdul Arif; Purwiyanti Purwiyanti (Journal of English Language Teaching and Education (JELTE), 2023)
This research was aimed to provide supplementary English Language modul for students English village in Parit Nanas village who do not have experience learning English at school. This study used development of the ADDIE model which includes 5 stages, namely Analysis, Design, Development, Implementation, and Evaluation. The research subjects were school students in Parit Nanas. There are 22 students who take part in the English Village program. The sampling technique used was a purposeful sampling technique. The instruments used in this study were student worksheets, student response questionnaires and expert validation sheets. The results of the study based on the data collection showed that the level of validation of the LKS from the material and graphic aspects was with an average value of 68,75 % with feasibility including criteria. While the practicality of the Genre-Based LKS on the English Village Parit Nanas student material is with an average value of 79,4 % which is included in the practical criteria. From the results of the study, it was concluded that the use of teaching materials in the form of worksheets can help students to be able to develop basic English skills so that they can be applied in their social context.